The genesis of the category «personal data» - Сопілко, Ірина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article describes sources and genesis of an important phenomenon of a democratic society – personal data and analyzes the main milestones of formation of legal regulation.